Research review on hydropower-wind power-photovoltaic multi-energy coupling power prediction technology. Issue 1 (1st October 2022) - Zhang, Feng; Zhang, Yi; Qiu, Yutao; Wu, Xiaogang; Tao, Yufeng; Ji, Qingfeng
Abstract: Energy shortage and environmental pollution have become the world's difficult problems, and the development of clean energy has become an inevitable choice. Solving the high proportion of clean energy consumption will become a major issue in the energy field. Various types of energy sources such as hydropower-wind power-photovoltaic power have coupling characteristics in certain geographical areas, and making good use of these coupling properties can better solve its joint prediction problem. This paper first introduces a brief situation of the development of these fields, proposes the main popular computing methods in this field, and conducts targeted analysis for the mainstream methods such as joint prediction, artificial intelligence and clustering algorithm, and finally puts forward the work value and conclusion of multi-energy coupling prediction.